Radiotherapy of ocular disease - Wiegel, Thomas; Bornfeld, Norbert; Foerster, Michael H.; Hinkelbein, Wolfgang (Frontiers of radiation therapy and oncology, 1997)
This book discusses current controversial topics and therapeutic strategies in the treatment of malignant and benign ocular diseases, with special emphasis on ocular tumors. Written by leading specialists, the articles highlight the latest developments in the diagnosis and therapy of retinoblastomas, uveal melanomas and malignant lymphomas. Further contributions include such topics as the optimization of dosimetry and design of radioactive eye plaques, the effects and side-effects of radiotherapy of age-related macular degeneration, and new approaches for perioperative organ-preserving brachytherapy for orbital tumors. Readers will be particularly interested in the discussion of possible side-effects of photon and proton beam radiotherapy of the eye and their minimization. Extensive data from clinical studies evaluating radiotherapy in the management of endocrine orbitopathy are also provided. The final part is dedicated to radiotherapy of benign ocular diseases such as pterygium or choroidal and retinal hemangiomas. Compiling the most up-to-date and comprehensive information on ocular radiotherapy currently available and offering an interdisciplinary perspective, this book will be appreciated by ophthalmologists, radiotherapists and oncologists.
Keywords: Konferenzschrift; Strahlentherapie; Augentumor; Augenkrankheit